Fragmentation of International Law: The Judicial Perspective - Treves, Tullio (2009)
The term «fragmentation» designates the breaking up, the reduction to fragments, of something that was a whole. It implies the factual premise, that indeed, before it was fragmented, something unitary existed and the value judgment that fragmentation is bad while unity is good. Debates about fragmentation of international law started without discussing the factual correctness of the unity of international law and saw fragmentation with concern, as a risk to be avoided.